A Grotesque Terracotta Figurine of the First Century C.E. from Muralto, Ticino, Switzerland: Function, Use, and Meaning - Simone Voegtle (Les Carnets de l’ACoSt)
A Roman terracotta figurine representing a grotesque ithyphallic male figure with the characteristics of a cock is discussed in relation to its role as an apotropaic device.